Analysis of nonlinear partial differential equation of traveling wave solutions with an effective method - Alkan, Asli; Bulut, Hasan; Akturk, Tolga; Engin, Oznur; Gulluoglu, Nesrin (Yildiz Technical Univ, 2025)
In this paper, the exact solutions of the (2+1)-dimensional generalized Hirota-Satsuma-Ito equation are acquired via the modified exponential function method. The method facilitates the acquisition of diverse solution functions under varying conditions, enabling the investigation of the linear mathematical model's behavior from multiple perspectives. Consequently, after deriving the solution functions that characterize the behavior of the nonlinear mathematical model, the plots of these functions have been plotted using the relevant parameters.
Keywords: Exact Solution; Hirota-SatsumaIto Equation; Modified Exponential Function Method